Menanamkan Kesiapan Masyarakat Terhadap Ancaman Bencana Tanah Longsor Di Desa Karangbanjar-Bojongsari Kabupaten Purbalingga - Asmoro Widagdo; Indra Permanajati; Hari Utama (Fakultas Sains Dan Teknologi, Universitas Raden Rahmat Malang, 2024)
Entering the rainy season in some areas of Karangbanjar Village, Bojongsari District, Purbalingga Regency which has steep slopes, it will potentially experience landslides. This phenomenon continues to be socialized to residents of vulnerable areas, at the beginning of the rainy season through field counseling by gathering several residents at meetings in villages to reduce risks and losses in the event of a landslide. This activity is carried out through the geological study of the area of socialization, field observations and counseling to residents. Factors causing landslides that were socialized to residents include slopes around settlements, constituent rocks, thickness of soil, rainfall and land use that can cause landslides. Keywords: rain, landslide, slope, counseling, soil.